Material characterization of additive manufactured parts for failure analysis and property improvement - Lee, Annabelle Yun Jin (Nanyang Technological University, 2020)
Selective Laser Melting (SLM) is a form of Additive Manufacturing (AM) that utilizes Powder Bed Fusion technology to melt atomized metallic powders to form 3-Dimensional parts. This technology allows the manufacturing of complex parts that eliminates material wastage. Although the technology is very advanced, there are instances where the part produced, its qualities might not be as desired. While a good set of process parameters are chosen for the building process, the parts will result in a significant variation of mechanical properties and the quality achieved. This brings up an issue where high-density parts produced are not consistent with every print. This project investigates the quality of parts that were built with the same process parameters and in the different sections of the SLM building chamber. Parts that were examined were prepared meticulously in order to obtain images and analysis at the micro level. This step will produce accurate results in the porosity and microstructure analysis which were done in order to identify the defects present in the parts and what factors could have caused it and to determine which section built the part with the highest density.